Masonería y política en Madrid (1900-1939) - Según-Alonso, Manuel (2019)
The researcher Manuel Alonso has defended a Doctoral Thesis in History, whose title is "Masonería y política en Madrid (1900-1939)" at the University of Distance Education (UNED) in Spain, on October 2, 2018, under the address of Juan Avilés Farré.